Helmut Schmidt and British-German relations : a European misunderstanding - Häußler, Mathias, 1988- 1988- (Cambridge University Press, 2019)
The young Helmut Schmidt and British-German relations, 1945-74 -- Harold Wilson, 1974-76 -- James Callaghan, 1976-79 -- Margaret Thatcher, 1979-82